Assessment of Hydroxyethyl Starch (6% HES 130/0.4) Kidney Storage in Critically Ill Dogs: A Post-mortem Prospective Study - Adamik, Katja-Nicole; Stoffel, Michael H.; Tangermann, Simone; de Breuyn Dietler, Bettina; Stokar-Regenscheit, Nadine (Frontiers in Veterinary Science, 2022)
Objective: Intravenous hydroxyethyl starch (HES) solutions are potentially nephrotoxic due to rapid renal tissue uptake, subsequent osmotic nephrosis, and long-lasting intracellular storage. This study aimed to investigate the severity of intracellular storage of HES in renal tissue samples from critically ill dogs receiving 6% HES 130/0.4. Materials and Methods: Fresh, post-mortem (<2 hours after death) renal tissue samples were analyzed through histology, immunohistochemistry (HES 130/0.4-specific antibodies), and electron microscopy for the severity of renal tubular vacuolization (VAC), intravacuolar HES accumulation (ACC), and ultra-structure impairment. Moreover, we investigated the relationship between VAC or ACC grade and HES dose (mL/kg), duration of HES administration (h), and pre-HES plasma creatinine concentrations. Results: Histology revealed that 2/20 dogs (10%) had no, 11/20 dogs (55%) had mild, 5/20 dogs (25%) had moderate, and 2/20 dogs (10%) had severe VAC. Immunohistochemistry revealed that 5/20 dogs (25%) had no, 6/20 dogs (30%) had mild, 7/20 dogs (35%) had moderate, and 2/20 dogs (10%) had severe ACC. Both changes were predominantly found in the distal tubular epithelium of mild and moderate cases, and all tubular segments were affected in severe cases. Seven of 20 dogs (35%) had osmotic nephrosis (ON). On electron microscopy, large granules with an electron-dense content were repeatedly detected in individual cells, mainly in the distal tubules. No correlation was found between cumulative HES dose or duration of HES administration and VAC grade, ACC grade, or presence/absence of ON. Conclusion: A high percentage of dogs had renal tubular HES storage and one-third of dogs showed HES-induced ON. Short-term HES administration caused VAC and ACC, regardless of the dose or duration of administration. In contrast to previous studies, HES 130/0.4 deposits were mainly located in the renal distal tubule.